'Take Notice of the Red Light!' A history of adult cinemas in Rome. Issue 1 (1st January 2017) - Bowen, Edward
This article presents a history of the rise and fall of adult cinemas in Rome. Primarily through research of the newspaper L'Unità's digitized archive and an interview with Rome's leading adult film exhibitor, I discuss the proliferation of adult cinemas, patterns in programming at each cinema, as well as their locations and audiences. I argue that adult film exhibition in Rome was not a marginal or peripheral phenomenon and that audiences, even if mostly male, were rather diverse. Beyond the videocassette boom, this article identifies government-led raids as a main catalyst in closing many adult cinemas. I argue that Mayor Francesco Rutelli's administration forced the closures of six adult cinemas near the Termini train station in the mid-1990s as part of an urban renewal campaign. This case exhibits many parallels with the campaign, piloted by leaders in New York City, to close adult cinemas near Times Square.